Bias and illumination-dependent room temperature negative differential conductance in Ni-doped ZnO/p-Si Schottky photodiodes for quantum optics applications - Ocaya, Richard O.; Orman, Yusuf; Al-Sehemi, Abdullah G.; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Cell Press, 2023)
In this article, evidence for the existence of illumination and bias-dependent negative differential conductance (NDC) in Ni-doped Al/ZnO/p-Si Schottky diodes, and the possible mechanism for its origin, are presented. The atomic percentages of Ni doping were 0%, 3%, 5%, and 10%. NDC is observed between-1.5 V to-0.5 V in reverse bias under illumination, but only at certain doping levels and specific forward bias. Furthermore, the devices show excellent optoelectronic characteristics in the photoconductive and photovoltaic modes, with device open circuit voltages ranging from 0.03 V to 0.6 V under illumination.
Keywords: Negative differential conductivity; Series resistance compensation; Ni-doped ZnO; Illumination; Bias